Psikoedukasi Bagi Guru Pembimbing Khusus (GPK) dalam Pengelolaan Emosi dan Keyakinan Diri Mendampingi Anak Berkebutuhan Khusus di Sekolah Inklusi - Rozi Sastra Purna; Yoszya Silawati; Fitri Angraini (Warta Pengabdian Andalas, 2023)
Teachers are essential for children with special needs, especially shadow teachers. The GPK's duties and responsibilities are to guide and direct children with special needs during inclusive schools' teaching and learning process. However, sometimes shadow teachers feel helpless, irritable, anxious, easily give up when faced with challenging assignments, and are slow to recover feelings of ability after experiencing failure. Therefore, understanding and psychoeducation are needed for teachers to increase their self-confidence. Psychoeducation aims to increase understanding regarding appropriate methods of managing emotions and increase self-confidence in dealing with children with special needs. Psychoeducation was delivered by lecture method. This series of activities consisted of several sessions. The first session was an introduction and an explanation of the purpose of psychoeducational activities so that activities were more focused. The next session provided material related to emotional management and self-confidence. The participants in this activity were 18 Special Guidance Teachers in the City of Padang. Measurement of emotion regulation refers to Thompson (1994), with a reliability value of 0.701. Self-efficacy measurement is based on the concept put forward by Bandura (1997), with a reliability value of 0.842. After receiving psychoeducation, 18 subjects (100%) were in the high category, and there were no subjects with low or moderate categories on emotion regulation and self-confidence.